Studies of the ice regime in the waters of the Gulf of Khatanga in the Laptev Sea - K. A. Kornishin; P. A. Tarasov; Ya. O. Yefimov; Yu. P. Gudoshnikov; S. M. Kovalev; Ye. U. Mironov; Ye. I. Makarov; A. V. Nesterov (Лëд и снег)
The study was carried out to reveal characteristics of the ice regime of poorly explored water area of the Khatanga Bay in the South-Western part of the Laptev Sea. Actuality of the research is due to the high potential of hydrocarbon reserves in the license area «Khatangsky» of the PAO «NK «Rosneft Currently available methods of monitoring ice cover and hydrometeorological conditions throughout the year were used. The main features of the hydrological regime of the region in the ice-free period, reflected in the spatial distribution of thermohaline characteristics and sea level fluctuations, are shown. The area under investigation has specific features of the conditions for the formation of ice cover: the entire area is covered with the fast ice; the winter fresh water infl w from Khatanga and Anabar rivers results in the desalination of sea water, and this promotes formation of ice cover, which differs in crystal structure and texture from both fresh and sea ices. These factors do influence on the mechanical properties of ice, including its strength. It was found that the average and maximum values of strength of the smooth and deformed ice of the Khatanga Gulf are approximately twice as high as the similar values of the sea ice strength in the southern part of the Laptev Sea. The basic features of the spatial distribution of different types of deformations of the ice cover such as lines of ice hummocks, zones of homogeneous ice hummocking, and stamukhas had been determined.